Cryptic maternal effects in Hippodamia convergens vary with maternal age and body size. Issue 2 (7th December 2012) - Vargas, German; Michaud, J.P.; Nechols, James R.
Abstract Maternal effects can mold progeny phenotypes in various ways and may constitute ecological adaptations. By examining the effect of oviposition sequence on progeny produced by different size classes of female ladybird beetles (produced by controlling larval access to food), we show that maternal signals can change through adult life and alter the developmental programs of progeny, ostensibly to synchronize their life histories with predictable resource dynamics, thus maximizing maternal fitness. We also show that female body size, as determined by larval food supply, interacts with female age to influence progeny fitness. When fed ad libitum as adults, small females reared with limited food access laid fewer, smaller eggs than large females reared with ad libitum food access. Maternal body size interacted with oviposition sequence to influence progeny development, but the latter had greater impact. Eggs laid later by medium and large females hatched faster than those laid earlier, larvae fed longer in the fourth instar, their pupation period was shorter, total developmental time was reduced, and adults emerged with greater mass, most notably daughters. Oviposition sequence effects on progeny from small mothers were non‐significant for total developmental time and progeny mass. Only large mothers increased egg size over time and egg mass was not consistently correlated with developmental parameters, indicating that progeny phenotype was impacted by other, more cryptic, maternal signals. Such signals appear costly, as food limitation during development constrained not only fecundity and egg size but also maternal ability to manipulate progeny phenotype. The production of faster‐developing offspring that mature to larger sizes late in the oviposition cycle may be adaptive for exploitation of ephemeral aphid outbreaks with predictable dynamics of prey abundance and competition.